2013
DOI: 10.4103/0975-7406.113302
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of disinfection effect of exposures to ultra-violet light and direct current glow discharge on Candida Albicans colonies coated over elastomeric impression material: An in vitro study

Abstract: Aim:The aim of our study is to compare the efficacy of ultra-violet light (U-V light) and direct current glow discharge in disinfecting Candida Albicans coated elastomeric impression material.Materials and Methods:Two hundred and forty samples of addition silicone material in the form of circular discs measuring (diameter-30 mm, thickness-3 mm) were prepared. Samples were divided into four groups namely A, B, C, D, with each group containing 60 samples. All samples in each group were sub grouped as follows for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
3
Order By: Relevance
“…The direct‐current glow discharge sustains the discharges in the range of milliamps to tens of milliamps. Direct‐current glow discharge has been shown to decrease the count of C. albicans colonies, but UV light could be a better disinfection method than direct‐current glow discharge …”
Section: Analysis Of Sterilization Methodsmentioning
confidence: 99%
“…The direct‐current glow discharge sustains the discharges in the range of milliamps to tens of milliamps. Direct‐current glow discharge has been shown to decrease the count of C. albicans colonies, but UV light could be a better disinfection method than direct‐current glow discharge …”
Section: Analysis Of Sterilization Methodsmentioning
confidence: 99%
“…Energy is generated during the glow discharge/plasma cleaning procedure, which could clean the surface being exposed. 32,33 This has been proved to be useful in the sterilization of implants and various studies supporting the same have been reported. Radiofrequency glow discharge is much handy and convenient procedure than immersion disinfection and spray atomization, which are the most commonly used modes of disinfection for impression materials.…”
Section: Discussionmentioning
confidence: 99%
“…Możliwość zarażenia chorobą zakaźną pracowników stomatologicznych wszystkich szczebli, a także pacjentów, wymogła konieczność stosowania skutecznych środków i metod dezynfekcji, tak aby spełniona była jedna z fundamentalnych zasad medycyny: primum non nocere. 1,2 Wyniki najnowszych badań dowodzą, że 67% materiałów przekazywanych do laboratorium protetycznego jest zainfekowanych mikroorganizmami. Najczęściej izolowanymi patogenami są: Streptococcus sp; Staphylococcus sp; Escherichia coli sp; Actinomyces sp; Antitratus sp; Pseudomonas sp; Enterobacter sp; Klebsiella pneumoniae i Candida sp.…”
Section: Wprowadzenieunclassified
“…Promieniowanie to jest niewidzialne dla człowieka, a jego nazwa pochodzi z łacińskiego słowa ultra (ponad, poza) oraz od słowa "fiolet", oznaczającego barwę o najmniejszej długości fali w świetle widzialnym. Ze względu na skutki działania na organizmy żywe, promieniowanie ultrafioletowe dzieli się na trzy typy: UV-A, UV-B oraz UV-C. 1,25,28,31 W stomatologii ultrafiolet może być stosowany jako metoda dezynfekcji wycisków. Coraz liczniejsze badania naukowe dowodzą jego skuteczności w tym zakresie.…”
Section: Promieniowanie Ultrafioletoweunclassified